Research handbook on child soldiers - Drumbl, Mark A.; Barrett, Jastine C. (Research Handbooks in international law series)
"Although child soldiers have received considerable media and policy attention, they remain poorly understood and inadequately protected. This Research Handbook addresses this troubling gap by offering a reflective and nuanced review of the complex issue of child soldiering, Containing original contributions from leading experts in many disciplines working across six continents, this comprehensive Handbook showcases diverse experiences and unique perspectives. The Handbook unpacks the life-cycle of youth and militarization: from recruitment, to demobilization, and return to civilian life. Challenging prevailing assumptions and conceptions, this uplifting Handbook focuses on the child soldier's capacity to cope with adversity. In so doing, it emphasizes the resilience, humanity and potential of children affected - rather than 'afflicted' - by armed conflict. The Research Handbook on Child Soldiers will be of interest to academics, practitioners and activists alike, with its extensive incorporation of cutting-edge fieldwork and the voices of the children themselves. Promoting equity between generations, this Handbook will also appeal to individuals from many walks of life who are concerned with the rights of the child in times of conflict, peace, and the in-between"--